Caracterização de hipersuperfícies tipo espaço com curvatura média constante e duas curvaturas principais no espaço anti de Sitter - Pereira, Wanderley de Oliveira (2013)
The aim of this work is to provide a characterization complete spacelike hypersurfaces in anti de Sitter space, such as hyperbolic cylinders, under the assumption constant mean curvature and two distinct principal curvatures. In the case that one of the principal curvatures is simple, a condition is added on the curvature. The characterization suggested here had as main reference the work of B.Yang and X. Liu, giving a positive answer to the L. F. Cao and G. Wei’s conjecture on spacelike hypersurfaces in such conditions. To carry out the work, we used a formula of type Simons along with the Generalized Maximum Principle (Omori-Yau).